Making media foundations of sound and image production - Roberts-Breslin, Jan
"Taking essential media production processes, this book deconstructs them into the most basic components. Students will learn the basic concepts of media production - frame, sound, light, time, motion, and sequencing - and be able to apply them to any medium they choose, from film and television to fine art and online applications. They will also become well-grounded in the digital work environment and the tools required to produce media in today's digital environment. This new fifth edition is fully updated throughout featuring updates on technology and processes. Included is new information on shooting with a cell phone, developments in mirrorless cameras, color grading, tips for recording good audio, intimacy training and much more. Fully illustrated, this book includes sidebar discussions of pertinent issues throughout. Readers will become well-grounded in the digital work environment and the tools required to produce media today, the primacy of content and the importance of an ethical approach to media making are emphasized. Features a companion website with interactive exercises for each chapter, allowing students to explore the process of media production. Ideal for media students on courses including media production, film production, audio production, and photography"--Provided by publisher.